The Role of Genetics in Inhibitor Formation - Gill, Joan Cox (Thrombosis and Haemostasis, 1999)
Treatment of hemorrhages in patients with inherited severe hemophilia A is dependent on transfusion replacement therapy with either plasma-derived or recombinant factor VIII concentrates.1 Hemorrhages become very difficult to treat after inhibitors develop, resulting in significant decreases in qualityof- life and life expectancy.2-6 Strategies to treat hemorrhages in the face of an inhibitor include the use of “bypass” therapy with activated and nonactivated prothrombin complex concentrates, high-dose factor VIII, porcine factor VIII, and recombinant factor VIIa. None of these is as effective as treatment of the noninhibitor patient with factor VIII.2,6 Therefore, several strategies to induce tolerance to factor VIII administration have been attempted, including administration of daily high-dose intravenous infusions of factor VIII concentrate alone, or in combination with, immune-modulating therapy.2,6 These strategies are extraordinarily difficult and expensive and are frequently unsuccessful, particularly when the inhibitor is well established. Thus, the ability to predict which patients are at risk for inhibitor development and to identify factors that predispose to inhibitor development would allow investigation of therapies targeted to prevent the establishment of the inhibitor response or to provide the ability to initiate early and, thus, more effective, immune tolerance induction for those at risk.